Pencegahan Stunting: Pemenuhan Nutrisi, Pendidikan Kesehatan dan Sosial Ekonomi dalam Upaya Penanggulangan Masalah Gizi pada Balita - Dika Saraswati; Faradita Wahyuni; Manik Wynda Myke Nola (Faletehan Health Journal, 2025)
Around 7.8 million of the 23 million children under five in Indonesia were stunted. The Indonesian government was committed to overcoming stunting, as stated in the national strategy plan for stunting prevention by 2018-2024. This study aims to examine stunting prevention strategies through the integration of nutrition, health education and socio-economic status in a vulnerable group, namely toddlers, in priority locations. The research method used is qualitative descriptive. The data were collected through interviews, documentation and observations to informants who were considered to know the importance of nutrition in the first 1000 days of birth as an effective intervention on child growth. Education and parental involvement in managing children's diets have an effect on stunting risk. Nutritional education to parents can play an important role in changing family eating behaviors. Successful interventions in addressing stunting involve a combination of strategies, including supplementation, nutritional supplementation, dietary changes and educational campaigns. Stunting prevention through improving nutritional fulfillment requires a holistic approach that involves various aspects, including nutritional education, access to quality food sources, supportive nutrition policies, and public understanding of the importance of a balanced diet.